THE RHETORICAL ANALYSIS ON THE TERRORISM DISCOURSE (A Study on Pronoun, Metaphore and Metonymy, and Cadence to Bush’s Discourse) - Abd. Muqit (IAIN MADURA, 2011)
This paper focuses on pronoun, methaphore, and metonymy, and cadency to Bush’s discourse, arguably one of the most compelling and contentious issues in rhetorical analysis. It explores the relationship between language and concepts of ideology and power in the linguistic practices of contemporary society through a critique of a critical discourse analysis (CDA) approach to linguistic enquiry, as evidenced in a study and brief review of one of its major practitioners, Norman Fairclough and Ruth Wodak. Essential differences with other mainstream linguistic approaches are emphasized in exploring and explaining the social basis of the ideological and power dimensions that underpin discourse in society, especially speech given by some one. It is maintained that the development of a critical linguistic awareness, which informs a capacity to resist and change exploitative and dominating linguistic practices, is an issue which should be of importance to everyone with a concern and interest in the problems of our contemporary society.